Morbidity and Mortality in Preterm Infants following Antacid Use: A Retrospective Audit - Natasha Singh; Aparna Dhayade; Abdel-Latif Mohamed; Tejasvi Vasant Chaudhari (International Journal of Pediatrics)
Background and Objectives. Antacids are often prescribed to preterm infants due to misdiagnosis of gastro-oesophageal reflux. This suppresses gastric acidity, a major defence mechanism against infection. This study aims to determine if ranitidine and omeprazole use in very low birth weight (VLBW) neonates, <1500 grams, is associated with increased risk of late onset sepsis, necrotising enterocolitis (NEC), and mortality. Methods. Retrospective analysis was conducted on neonates, <1500 grams, born and admitted into the Neonatal Intensive Care Unit at The Canberra Hospital during the period from January 2008 to December 2012. Information regarding late onset sepsis, NEC, mortality, ranitidine/omeprazole use, and other neonatal/hospital factors was collected for each neonate. Results. 360 neonates were evaluated, 64 received ranitidine and/or omeprazole, and 296 had not. There were no statistically significant differences in incidence of late onset sepsis (OR = 0.52, CI = 0.24–1.1, and p = 0.117), NEC Stage 2 and above (OR = 0.4, CI = 0.05–3.2, and p = 0.7), or mortality (OR = 0.35, CI = 0.08–1.5, and p = 0.19) between the two groups. After adjusting significant differences in neonatal and hospital factors, risk of late onset sepsis was significantly lower in those that received ranitidine/omeprazole (OR = 0.28, CI = 0.13–0.65, and p = 0.003). Conclusions. Ranitidine and omeprazole use in VLBW preterm infants may not be associated with an increased risk of infection, NEC, and mortality.